Platelet Reactions and Immune Processes - Jobin, F; Tremblay, F (Thrombosis and Haemostasis, 1969)
We have studied the effect of complement inhibitors of various classes on platelet aggregation induced by collagen or by latex. The majority of the complement inhibitors which we studied inhibited collagen- or latex-induced platelet aggregation.The possible role of complement as a mediator in the activation of platelet reactions is discussed.These findings indicate that some chemicals are able to act on some of the immune reactions and also on platelet thrombogenetic reactions. It is suggested that drugs or combination of drugs having such a polyvalence might be of particular benefit in thrombo-immuno-inflammatory conditions.